Mafias y tráficos ilícitos: tráfico ilícito de arena - Oliver, Francisco Xavier Moreno (Quadernos de criminología, 2021)
Sand is the most widely used raw material, second only to water. The demand for this arid, by construction companies and different sectors of the industry, is higher than can be obtained in a sustainable way. Sand is not an infinite resource. This has led to the emergence of a black market supplying this type of mineral.